Electronic patient information systems and care pathways: The organisational challenges of implementation and integration. (September 2014) - Dent, Mike; Tutt, Dylan
Our interest here is with the 'marriage' of e-patient information systems with care pathways in order to deliver integrated care. We report on the development and implementation of four such pathways within two National Health Service primary care trusts in England: (a) frail elderly care, (b) stroke care, (c) diabetic retinopathy screening and (d) intermediate care. The pathways were selected because each represents a different type of information and data 'couplings', in terms of task interdependency with some pathways/systems reflecting more complex coordinating patterns than others. Our aim here is identify and explain how health professionals and information specialists in two organisational National Health Service primary care trusts organisationally construct and use such systems and, in particular, the implications this has for issues of professional and managerial control and autonomy. The article is informed by an institutionalist analysis.